The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/d12110409
|View full text |Cite
|
Sign up to set email alerts
|

Poor Correlation between Diamondback Terrapin Population Estimates Using Two New Estimation Methods

Abstract: Reliable estimates of animal and plant population sizes are necessary to track trends in populations through time. Diamondback terrapins are an ecologically unique keystone species that are globally declining. Conservation efforts for this species rely on accurate estimates of population sizes; however, diamondback terrapin population size estimates are difficult to measure with precision or accuracy. Terrapin collection methods are often labor-, time-, and cost-intensive. The present study compares two recent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 26 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…Byers et al (2011) and Eugene (2019) found that both cyst abundance and cyst prevalence were positively correlated with the sizes of nearby nesting female terrapin populations. However, Prowant and Burke (2020) reported that cyst counts were not correlated with head counts, another newly developed terrapin census technique. Because participant counts of cysts were not always accurate, we suggest that groups focusing on determining intensities should be provided more training on counting of cysts (particularly cysts on the operculum of mudsnails).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Byers et al (2011) and Eugene (2019) found that both cyst abundance and cyst prevalence were positively correlated with the sizes of nearby nesting female terrapin populations. However, Prowant and Burke (2020) reported that cyst counts were not correlated with head counts, another newly developed terrapin census technique. Because participant counts of cysts were not always accurate, we suggest that groups focusing on determining intensities should be provided more training on counting of cysts (particularly cysts on the operculum of mudsnails).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, records of “infected” snails are not correct in some reports (e.g. Demetriades, 2020; Prowant & Burke, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Making turtle censuses easier yet accurate can facilitate conservation. Two of the papers [6,7] focus on interesting new techniques (visual head counts and surveys of parasitic trematodes) for surveying diamondback terrapins (Malaclemys terrapin), a declining species listed as Vulnerable by the IUCN [8]. Like many turtles, terrapin population trends are difficult to measure with precision or accuracy, and these new techniques offer easier methods, which are even usable by citizen scientists.…”
mentioning
confidence: 99%